Pembiayaan Usaha Super Mikro di Bank Zakat: Perspektif Maslahah Mursalah - Hartono, Haryani Santo (SIL'AH: Jurnal Ekonomi Syariah, 2024)
Indonesia as the country with the largest Muslim population, which is also the most generous country in the world, has the potential to raise Islamic philanthropy funds quite high and continues to increase every year. However, Indonesia, as developing country, still has quite high poverty rates. The reality is that there is still a lot of circulation of loan funds from money lenders among the lower middle class, including those used as business capital. This is experienced evenly in almost all regions in Indonesia. This includes one of the districts in South Sumatra province, Musi Rawas. BANKZAKAT appeared as a program institution from BAZNAS Musi Rawas Regency. This research explains the concept of super micro business financing at BANKZAKAT and analyzes it from the maslahah mursalah perspective. This research uses a qualitative approach and descriptive analysis methods. Collect data through observation and literature study. This research analyzes the concept of financing model in terms of realizing policies for equal distribution of the economy, as well as community empowerment and development. It is hoped that the micro and super micro scale business financing models used can create an economic empowerment ecosystem for all levels of society.